2012
DOI: 10.1152/ajpendo.00167.2012
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with constitutive androstane receptor ligand during pregnancy prevents insulin resistance in offspring from high-fat diet-induced obese pregnant mice

Abstract: The constitutive androstane receptor (CAR) has been reported to decrease insulin resistance even during pregnancy, while exposure to a high-fat diet (HFD) in utero in mice can induce a type 2 diabetes phenotype that can be transmitted to the progeny. Therefore, we examined whether treatment with a CAR ligand during pregnancy could prevent hypertension, insulin resistance, and hyperlipidemia in the offspring from HFD-induced obese pregnant mice (OH mice). We employed four groups of offspring from HFD-fed and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…The metabolic benefits of CAR activation may have resulted from the combined effect of inhibition of lipogenesis, very low density cholesterol secretion and export of triglycerides, and gluconeogenesis; increases in brown adipose tissue energy expenditure and peripheral fat mobilization may have also played a role. Similar effects of CAR activation in relieving high-fat diet and ob/ob models of steatosis and type 2 diabetes (Dong et al, 2009) and gestational obesity and diabetes (Masuyama and Hiramatsu, 2012a;Masuyama and Hiramatsu, 2012b) have been independently reported. These results have revealed an important metabolic function of CAR and may establish this "xenobiotic receptor" as a novel therapeutic target for the prevention and treatment of obesity and type 2 diabetes.…”
Section: Endobiotic Functions Of Xenobiotic Receptors and Xenobiotic supporting
confidence: 62%
“…The metabolic benefits of CAR activation may have resulted from the combined effect of inhibition of lipogenesis, very low density cholesterol secretion and export of triglycerides, and gluconeogenesis; increases in brown adipose tissue energy expenditure and peripheral fat mobilization may have also played a role. Similar effects of CAR activation in relieving high-fat diet and ob/ob models of steatosis and type 2 diabetes (Dong et al, 2009) and gestational obesity and diabetes (Masuyama and Hiramatsu, 2012a;Masuyama and Hiramatsu, 2012b) have been independently reported. These results have revealed an important metabolic function of CAR and may establish this "xenobiotic receptor" as a novel therapeutic target for the prevention and treatment of obesity and type 2 diabetes.…”
Section: Endobiotic Functions Of Xenobiotic Receptors and Xenobiotic supporting
confidence: 62%
“…The modes of action for such inhibitory effects may include the following: (1) competitive binding to cis-acting elements; (2) coactivator quenching; and (3) induction of suppressive genes, leading to direct inhibition of certain transcriptional factors, deactivation of pro-diabetic agonists or production of anti-diabetic substances, and changes in metabolite profiles. In addition, the metabolic benefits can also be transmitted to offspring due to permanent epigenetic switches [105,106] . In summary, CAR is a potential therapeutic target for the prevention and treatment of metabolic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…It has long been known that phenobarbital reduces plasma fasting glucose and improves insulin sensitivity in diabetic patients (Lahtela et al, 1984). A few recent studies showed that activation of CAR by TCPOBOP improved hyperglycemia and insulin sensitivity in obese and diabetic ob/ob mice and high-fat diet-induced obese mice (Dong et al, 2009;Gao et al, 2009;Masuyama and Hiramatsu, 2012). It was reported that phenobarbital decreased the expression of PEPCK and G6Pase in both primary hepatocytes and mouse liver, suggesting that phenobarbital may inhibit hepatic gluconeogenesis (Kodama et al, 2004;Miao et al, 2006).…”
Section: Bile Acid Receptor Signaling In Liver Metabolismmentioning
confidence: 99%
“…A few recent studies have reported antiobesity and lipid-lowering effects of CAR agonists in mice (Gao et al, 2009;Sberna et al, 2011;Masuyama and Hiramatsu, 2012). The mechanisms by which CAR activation decreases weight gain is not clear, but reduced body weight gain in mice likely contributes to reduced hepatic steatosis and hepatic VLDL production and promotes the antiatherogenic lipid profile in mice treated with CAR agonists.…”
Section: Bile Acid Receptor Signaling In Liver Metabolismmentioning
confidence: 99%